2022
DOI: 10.3389/fnins.2022.843988
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hierarchical Auditory Representation via a Neural Encoding Model

Abstract: By integrating hierarchical feature modeling of auditory information using deep neural networks (DNNs), recent functional magnetic resonance imaging (fMRI) encoding studies have revealed the hierarchical neural auditory representation in the superior temporal gyrus (STG). Most of these studies adopted supervised DNNs (e.g., for audio classification) to derive the hierarchical feature representation of external auditory stimuli. One possible limitation is that the extracted features could be biased toward discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This approach has been embraced in vision studies which showed that deep neural networks trained on identifying objects reveal progressions of hierarchical processing from simple features like edges and textures to more complex object categories mimicking gradients of processing in the visual what stream (Güçlü & van Gerven, 2015 ). Similar insights about processing gradients in the auditory stream have been gleaned using deep learning methods that not only shed light on cortical processing hierarchies, but also specialized processing in non-primary cortical pathways for processing speech and music sounds (Kell et al, 2018 ; Wang et al, 2022 ). In the current study, deep neural networks were also used as an investigative tool to infer relationships between behavioral responses to natural auditory scenes and nonlinear abstractions of these scenes extracted by learned models.…”
Section: Introductionmentioning
confidence: 83%
“…This approach has been embraced in vision studies which showed that deep neural networks trained on identifying objects reveal progressions of hierarchical processing from simple features like edges and textures to more complex object categories mimicking gradients of processing in the visual what stream (Güçlü & van Gerven, 2015 ). Similar insights about processing gradients in the auditory stream have been gleaned using deep learning methods that not only shed light on cortical processing hierarchies, but also specialized processing in non-primary cortical pathways for processing speech and music sounds (Kell et al, 2018 ; Wang et al, 2022 ). In the current study, deep neural networks were also used as an investigative tool to infer relationships between behavioral responses to natural auditory scenes and nonlinear abstractions of these scenes extracted by learned models.…”
Section: Introductionmentioning
confidence: 83%
“…Additionally, a representational hierarchy of speech processing was apparent with intermediate layers mapping best to neural activity in PAC while later layers best predicted activity in adjacent regions along the temporal plane (Kell et al, 2018). This representational gradient was demonstrated to be independent of the learning modality, i.e., supervised or unsupervised learning in the neural network (Wang et al, 2019(Wang et al, , 2022.…”
Section: Future Outlook: Using Neural Network To Decode Pattern Of La...mentioning
confidence: 91%
“…The consumer assessment of firms' products promoted by radio ads depends on the mental representation of the message, modeled by sounds (auditory stimulus) (Lombardi Vallauri, 2017; Soto‐Sanfiel et al, 2021). Radio is considered an effective platform for creating images of the consumer mind, as the human brain can synthesize signals, catalog them, and coordinate them (Lezama‐Espinosa & Hernandez‐Montiel, 2020; Wang et al, 2022). This platform allows the use of different forms of audio branding such as audio logos, claim sounds, commercial songs, jingles, brand songs, brand voices, and product sounds (Barrio Fraile et al, 2021; Rodero & Larrea, 2020; Rodriguez et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%